Analisis Kebutuhan dan Perancangan Sistem Informasi Seleksi Perangkat Desa : Studi Kasus : Desa Kaleng Kec. Puring, Kab. Kebumen - Imam Tri Suryadin; Aang Anwarudin; Lazuardi Fatahilah Hamdi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focuses on the analysis and development of a web-based information system designed to support the selection process of village officials in Kaleng Village, Puring District, Kebumen Regency. The study aims to create a system that ensures transparency, accountability, and efficiency in the recruitment process, which has traditionally been conducted manually and prone to errors. The system development method follows the Waterfall model, consisting of four main stages: requirement analysis, system design, implementation, and testing. Data for system requirements were collected through interviews with stakeholders, direct observations of the existing manual process, and document studies of administrative procedures and regulations. The system developed provides several core modules to support the recruitment process, including user registration, administrative selection, written test stages, and final announcement features. Each module is designed to align with the operational needs of the village government while also incorporating mechanisms to reduce potential bias and increase accountability. The registration module simplifies the submission of applicant data, while the administrative selection module verifies eligibility criteria. The written test stage allows standardized evaluation of candidates, and the announcement module ensures that results are communicated transparently and fairly to all participants. The implications of the research indicate that the system can significantly reduce manual errors, minimize administrative inefficiencies, and strengthen public trust in the recruitment process at the village level. Furthermore, the web-based design enables accessibility for both applicants and administrators, ensuring that information is easily available and verifiable. This study concludes that the implementation of a web-based information system for village official selection represents a strategic step toward modernizing local governance processes, fostering transparency, and promoting accountability in rural administration.